(untitled) (Research, Society and Development, 2024)
The use of active methodologies for the teaching-learning process can enhance the student-student and teacher-student relationship because they are based on procedures that help in the construction of knowledge; that is, they enable students to develop skills related to autonomy and protagonism. With the aim of researching the training of mathematics teachers, this work, which is part of an investigation into teacher training in the Graduate Program in Mathematics Education (PPGEDMAT) at the Federal University of Ouro Preto (UFOP), had the general objective of understanding what teaching knowledge is mobilized through the peer instruction method in mathematics classes. To this end, the research was based on a qualitative approach in which the following research question was proposed: What teaching knowledge is mobilized through the peer instruction method in mathematics classes? This article presents a brief description of the peer instruction method, an active and collaborative learning methodology, considering its potential for the teaching and learning process in mathematics classes. As a result of the literature review, it was found that active methodologies, especially the peer instruction method, encourage students to think critically, question, analyze, and build robust knowledge about mathematics education.